THE EFFECT OF ENVIRONMENTAL FACTORS TO THE LOCAL GOVERNMENT PUBLIC SERVICES AT THE BORDER REGION - Arifin, Arifin; Rupita, Rupita (Universitas Padjadjaran, 2021)
One of the fundamental problems in the border area of Sanggau Regency is the infrastructure of roads and bridges. Those problems become more complex due to various aspects that affect the governmental institutions in implementing the public services are the community, environment, and other aspects. Based on the problems, the research aims is to describe and analyze the complexity effect of public basic services for roads and bridges by point of view of the external aspects of an organization. The research method used is qualitative design. Researchers try to focus on showing the meaning, description, classification and placement of data in their perspective contexts. The results of the study show that the main factors in which the public basic services are not optimal are the unfavourable local and socio-economic conditions of the community. The cost needed in basic public services is high enough because of the landscape range. It is exacerbated by the socio-economic constraints of the community which indirectly can hamper theprocess of running the public services provided. In overcoming of the two problems, the strategic effort that needed is better coordination amongst the organizations in the area. For example, The public works Services (Dinas Pekerjaan Umum) must be coordinated to the other government organization in implementing some programs.